A nonlinear moment-angle relation for the ski-boot hysteresis - Eberle, R.; Kaps, P.; Heinrich, D.; Mössner, M.; Hofer, P.; Schindelwig, K.; Nachbauer, W. (Science and Skiing VI. 6th International Congress on Science and Skiing, Dec. 14 - 19, 2013, St. Christoph am Arlberg, 2015)
Thus the purpose of this work was to measure ski-boot hysteresis, to develop an improved hysteresis model, and to implement the nonlinear fit for the moment angle relation of the ski-boot in the musculoskeletal simulation software of Heinrich et al., (2013). Resulting ACL loads were compared for the linear and nonlinear fit.